Language, migration, and ChatGPT - Catapang, Jasper Kyle; Borlongan, Ariane; Go, Mikhail Alic (Journal of Modern Languages, 2025)
This article examines how ChatGPT is reshaping the linguistic and social conditions of contemporary migration by situating its impact within discussions on integration, labor precarity, and the ethics of new technologies. It shows how large language models now participate in communicative tasks that migrants once managed solely through human interaction, including navigating government procedures, consulting medical professionals, and handling routine daily exchanges. These examples reveal how ChatGPT can broaden access to information while also producing errors that may create serious challenges for migrants who depend on reliable guidance. The article further considers how automation in service and clerical roles, many of which employ migrants, heightens existing job vulnerabilities. Ethical concerns such as misinformation, impersonation, bias, and opaque decision processes are treated as structural risks that affect migrants unevenly, especially when time, language resources, or institutional knowledge are limited. The discussion concludes by identifying digital competence as a necessary component of migrant integration, emphasizing the importance of understanding both the capabilities and the boundaries of ChatGPT. Through this perspective, the article contributes to migration linguistics by illustrating how AI systems are becoming part of the communicative environments that migrants must learn to navigate.